Persepsi Auditor Independen Atas Pengaruh Pengalaman Audit, Kompleksitas Tugas, Tekanan Ketaatan Dan Pengetahuan Terhadap Audit Judgment (Studi Empiris Pada Kantor Akuntan Publik di Wilayah Surakarta dan Semarang) - Yuniarti, Alief; , Wahyono, Drs, Ak, MA (2017)
This study aims is to examine and analyze the influence of audit experience, the complexity of the task, the pressure obedience and knowledge on audit judgment. The object of research is the auditors who work in public accounting firm in Surakarta and Semarang. The sampling technique used is convenience samplingwith a sample of 39 auditors obtained from seven public accounting firms. Data analysis method used is multiple linear regression analysis with SPSS version 21.0. The results showed that the experience of the audit and the complexity of the task has no effect on audit judgment, while the pressure obedience and knowledge has an influence on audit judgment. Keywords: audit experience, the complexity of the task, the pressure obedience, knowledge, audit judgment.